HCV in sickle cell disease. - Hassan, Mohamed (National Medical Association, 2003)
The sickle cell gene is common in the U.S. In fact 8% of African Americans are healthy carriers of the sickle cell trait (HbAS). People who are homozygous (HbSS) have severe disease. They have life-long anemia, chronic hemolysis, and also have at times hematological crises, which can worsen the anemia. Many patients require chronic transfusions and as a result, substantial proportions of sickle cell patients are at high risk for infection with blood-borne diseases-such as Hepatitis C Virus infection (HCV). The HCV antibody positivity is directly related to the number of transfusions given, and on average the prevalence rate in transfused patients is more than 10%. It is known that the combination of iron overload and HCV can lead to a more rapidly progressive liver disease. The treatment of HCV in sickle cell patients poses a challenge to clinicians. A novel approach described by some is the pre-treatment of these patients with hydroxyurea to increase the fetal hemoglobin, therefore decreasing the severity of Ribavirin-related hemolysis. Treatment with Peg-interferon alone has not been used to treat HCV in sickle cell patients, but in the setting of controlled clinical trials it would be feasible. This review explores the impact of HCV in sickle cell patients and the possible therapeutic options available to them.